Multifunctional quaternized carbon dots with enhanced biofilm penetration and eradication efficiencies. Issue 33 (29th July 2019) - Ran, Huan-Huan; Cheng, Xiaotong; Bao, Yan-Wen; Hua, Xian-Wu; Gao, Ge; Zhang, Xiaodong; Jiang, Yao-Wen; Zhu, Ya-Xuan; Wu, Fu-Gen
Abstract : Ultrasmall quaternized CDs are used to visualize Gram-positive and Gram-negative bacterial biofilms, and selectively eradicate and inhibit Gram-positive bacterial biofilms. Abstract : Biofilm formation can lead to the treatment failure of persistent bacterial infections. Although a variety of antibacterial agents have been developed, the restricted drug penetration and the embedded bacteria's potentiated recalcitrance to these agents synergistically lead to the unsatisfactory anti-biofilm effect. Herein, we report the applications of metal-free quaternized carbon dots (CDs) in imaging and eliminating bacterial biofilms. The CDs prepared by the solvothermal treatment of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (abbreviated as Si-QAC) and glycerol possess ultrasmall size ( ca. 3.3 ± 0.4 nm) and strong positively charged (zeta potential: ca. +33.1 ± 2.5 mV) surfaces with long alkyl chain-linked quaternary ammonium groups. The small size of the CDs endows them with the penetration ability into the interior of Gram-negative and Gram-positive bacterial biofilms, which enables excellent fluorescence imaging of the biofilms. Due to the different surfaces of the two types of bacteria, the positively charged CDs selectively interact with the more negatively charged Gram-positive bacteria via electrostatic and hydrophobic interactions, which inactivates the Gram-positive bacteria and ultimately eradicates the Gram-positive bacterial biofilms. In addition, we synthesize a new type of quaternized CDs without long alkyl chains (termed TTPAC CDs), and validate that the long alkyl chains potentiate the hydrophobic adhesion between CDs and Gram-positive bacteria. Meanwhile, the crystal violet staining results reveal that the cationic CDs inhibit the formation of Gram-positive bacterial biofilms. Collectively, our work highlights the feasibility of using cationic and ultrasmall metal-free CDs to eliminate and inhibit Gram-positive bacterial biofilms, which represents a highly effective strategy to cope with refractory biofilm-associated infections.